2018
DOI: 10.5958/0976-5506.2018.01583.8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing on dry eye symptoms of university students using smartphone

Abstract: This study is a descriptive study to investigate relevance of dry eye symptoms and physical symptoms of university students using smartphones and to identify the factors affecting dry eye symptoms. We collected data from university students in C province of Korea on March 3-29, 2016. They responded questionnaires of general characteristics, physical symptoms, and eye dry symptoms. 315 questionnaires were collected and 310 questionnaires were analyzed except for the incomplete one. Data were analyzed using t-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…The excessive and problematic usage of smart phones causes physical problems, for example, sleep problems (falling asleep late, awakening from sleep, etc. ; Demirci et al, 2015), eye health (Choi et al, 2018), musculoskeletal system (Kim & Kim, 2015), traffic and other severe accidents (Nasr Esfahani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The excessive and problematic usage of smart phones causes physical problems, for example, sleep problems (falling asleep late, awakening from sleep, etc. ; Demirci et al, 2015), eye health (Choi et al, 2018), musculoskeletal system (Kim & Kim, 2015), traffic and other severe accidents (Nasr Esfahani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The third study examined the relationship between SPU in hours measured using a self-reported cross-sectional questionnaire and DED measured based on both self-reported dry eye symptoms and clinical eye examination. [13] DED was defined and diagnosed according to the International Dry Eye WorkShop Choi et al, 2018 [21] South Korea NRT Young adults, population based 80 37.5 21-36 (25.96, 2.98) Choi et al, 2018 [20] South Korea CS College students 315 73.2 ≥18 (20.82, 5.66) Moon et al, 2014 [13] South Korea CS School children 288 50.7 11-12 (DED 11.00, 0.61; control 10.87, 0.66) Moon et al, 2016 [12] South Korea CS School children 916 53. 2007.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Not reported = 0 Reported but inadequate = 1 Reported and adequate = 2 Choi et al, 2018 [20] 0 1 0 1 2 1 1 6 Moon et al, 2014 [13] 1 0 0 1 2 2 1 7 Moon et al, 2016 [12] 0 0 0 1 2 2 1 6…”
Section: Study Quality Itemmentioning
confidence: 99%
“…Chapter 2: Evaluating questionnaires assessing contact lens dissatisfaction from contact lens discomfort and binocular vision disorders as a factor for DED, 81,[421][422][423][424][425][426][427][428][429][430][431][432][433] dry eye interventions involving CL use, 177,[434][435][436][437] therapeutic interventions while wearing CLs, 438 and to categorise CL wearers as those with or without CLD. 15 OSDI has also been shown to correlate with both CLDEQ-8 and CISS.…”
Section: Thesis Overviewmentioning
confidence: 99%